A systematic literature review of visualization in code clone detection models - Nur Fatin Syahidah, Mohd Zamri; Al Fahim, Mubarak Ali; Aziman, Abdullah; Siti Salwani, Yaacob (IEEE, 2026)
Code clones, which are instances of the same code segments copied in a software system, are created by developers for a variety of purposes. Code duplication is frequently brought on by programmers’ efficiency-seeking tendencies, which lead them to use copy-paste methods to speed up coding work. Numerous studies have proposed code clone visualization approaches to reduce code snippet replication and manage clone occurrences effectively. Visualization helps developers understand and avoid having duplicate code segments in software systems by giving them visual representations. Thus, in order to improve developers’ comprehension and stop the replication of code fragments, the present study provides a comprehensive evaluation of visualization approaches addressing code clone occurrences. The purpose of this study is to provide a systematic literature review of current code clone visualization approaches. The review and results of the study are presented, along with recommendations for further research projects that will enhance the current code clone visualization approaches.